Keadilan Gender dalam Hukum Pembagian Waris Islam Perspektif The Theory Of Limit Muhammad Syahrur - Muhammad Ali Murtadlo (INSTITUT AGAMA ISLAM BANI FATTAH (IAIBAFA), 2018)
The division of inheritance it refers to the verses of inheritance turns out to date still leaves unresolved problems, such as the 2:1 division between men and women who are considered gender biased. According Syahrur, inheritance legislation is time to change. Syahrur uses various methods in studying Islamic inheritance law, such as mathematical theory with reference to Newton's mathematical analysis theory. By the method of mathematical analysis, Syahrur formulated the boundaries of Allah's law which is termed with The Theory Of Limit. In this theory, there is an understanding of the limits of Allah's provisions that should not be violated, but within it there is a flexible area of ??ijtihad. According to him, QS. AnNisa 'verse 11 which explains the male's doubling part is the maximum and can not be added, while the woman is the minimum limit, so under certain circumstances a woman potentially has more share. The Limit Theory intends to state that the Qur'anic verse, always relevant to every situation and condition, and Islam is the last and universal religion directed to all mankind.